Function and Regulation of Nuclear DNA Sensors During Viral Infection and Tumorigenesis - Zhang, Fan; Yuan, Yi; Ma, Feng (Frontiers in Immunology, 2021)
IFI16, hnRNPA2B1, and nuclear cGAS are the nuclear-located DNA sensors, playing important roles in initiating host antiviral immunity and modulating tumorigenesis. IFI16 triggers innate antiviral immunity, inflammasome, and suppresses tumorigenesis by recognizing double-stranded DNA (dsDNA), single-stranded DNA (ssDNA), damaged nuclear DNA, or cooperatively interacting with multiple tumor suppressors such as p53 and BRCA1. hnRNPA2B1 initiates interferon (IFN)-a/b production and enhances STING-dependent cytosolic antiviral signaling by directly binding viral dsDNA from invaded viruses and facilitating N6-methyladenosine (m6A) modification of cGAS, IFI16, and STING mRNAs. Besides, nuclear cGAS is recruited to double-stranded breaks (DSBs), suppresses DNA repair, and promotes tumorigenesis. Here, we briefly describe the nuclear functions of IFI16, hnRNPA2B1, and cGAS, and summarize the transcriptional, post-transcriptional, and post-translational regulation of these nuclear DNA sensors.